Overview of Static Electricity in Some Industrial Operations with Petroleum Products - Igor’ S. Taubkin (Теория и практика судебной экспертизы)
Fires and explosions of petroleum products vapors triggered by static electricity discharges are not uncommon during various technological operations. Investigation of their role in accidents is one of the more labor intensive and complicated forensic tasks. The purpose of this work is to provide forensic experts with general information on electrostatic charging mechanisms in liquids and solids, as well as on production operations with petroleum products where static electricity may occur, leading to the ignition of their vapors.